Under the Background of Strengthening the Popularization of Science and Technology the Path to Improving Scientific Literacy among College Students in the New Era - Weng, Sijie (Journal of Educational Research and Policies, 2026)
To achieve Chinese-style modernization, we need to develop new quality productivity, which must be centered on scientific and technological innovation. Colleges and universities should focus on enhancing students’ scientific literacy, strengthening their scientific awareness and scientific literacy, so as to effectively enhance the country’s scientific and technological competitiveness. To enhance the scientific literacy of college students, schools should establish a sense of primary responsibility; At the student level, it is necessary to stimulate active learning interest; A collaborative education mechanism needs to be established at the social level. Through the joint efforts of schools, students and society, create a better environment and conditions for improving the scientific literacy of college students.